Identidad genética y estructura social del delfín Franciscana, Portoporia blainvillei, en el área sur de su distribución - Gariboldi, María Constanza (2017)
The franciscana dolphin, Pontoporia blainvillei, is a small cetacean with marine and coastal habits. Its distribution extends from Espíritu Santo (Brasil) to Río Negro (Argentina). It is\nclassified as Vulnerable by IUCN. Previous studies found genetically distinct populations along its distribution; although the southernmost portion of its rage still lacks information.\nThe goal of this thesis was to improve the knowledge about the population genetic identity, genetic variability and social structure of the species in the southern edge of its distribution. Samples from 74 individuals were collected from incidentally entangled or stranded franciscanas along the coastal area between Necochea and Río Negro; 5 samples from San Clemente del Tuyú and Pinamar were collected as well A fragment from the mitochondrial DNA control region, 10 microsatellite loci and fragments from ZFX and SRY were amplified.In the southern area of the species´ distribution, genetic information was combined with environmental and age data. Five novel mitochondrial haplotypes were found, totalizing 60\nhaplotypes described for the whole distribution area of the species. Higher levels of mitochondrial DNA diversity suggest a species´ colonization from La Plata Estuary towards\nthe extremes of its distribution. As in other areas of the species´ distribution, no evidence of\nsex-biased dispersal was observed in the southern area of its distribution. Three genetically distinct populations were found in the southernmost portion of the franciscana distribution,\ntotalizing 5 populations within Argentina and 10 along its distribution. The population from\nRío de Janeiro would be the only one that experienced a sudden expansion 60.000 years ago. An isolation by distance pattern exists when considering the entire distribution of the species,but not in the southern area. The population genetic structure in the latter area would not be explained by environmental data either; other factors might affect the population genetic\nstructure in the southernmost area of the species distribution. Also, random mating between\nindividuals and a lack of population substructure would exist; however, relatedness between\nindividuals within each population is significantly different than that observed between populations. This is the first study of the species where, within the same fish net, a father and\nits two same age offsprings where found: male franciscanas might prolong their bonds with\ntheir offspring at least until the first year of the offspring life, and the mating system might change in space and/or time. Results achieved in this thesis increase the population genetic and social structure knowledge of the species, which can be used to develop management and\nconservation plans that ensure the log-term survival of the species